Environmental Agreement as the Object of State Administrative Disputes - Teguh Triesna Dewa (Jurnal Cita Hukum, 2024)
The implementation of state administrative law is presently undergoing considerable changes due to modifications in environmental law regulations. A significant alteration is the shift from a business license framework to a business approval framework, which has generated ambiguity in environmental law enforcement, particularly incorporating ecological approvals under the purview of disputes in the State Administrative Court (PTUN). This alteration presents new difficulties in ascertaining the authority of the PTUN and the interpretation of environmental legislation within the framework of state administration. This study employs a qualitative research methodology utilizing two primary approaches: the literature approach and the legal approach. The literature approach examines several academic sources, journals, books, and legal documents pertinent to the evolution of the corporate licensing and approval system and its implementation in environmental law. This literature study elucidates the theoretical framework and legal advancements pertinent to ecological conflicts in the PTUN. The legal analysis involves scrutinizing relevant laws and regulations, particularly state administrative and environmental law, including Law No. 30 of 2014 on Government Administration and Law No. 32 of 2009 on Environmental Protection and Management. The study's findings indicate that transitioning from a business licensing system to a business approval system has generated ambiguity within PTUN authority, particularly on environmental approvals. The State Administrative Court, as a crucial judicial body under the Supreme Court, possesses autonomy in adjudicating administrative disputes and plays a key role in the enforcement of environmental law. Yet, this alteration necessitates a more explicit elucidation of environmental and state administrative law interplay. This article seeks to examine the function of the PTUN within the Indonesian legal system concerning the enforcement of environmental law and to provide solutions for addressing the issues stemming from this regulatory alteration.